Lissodendoryx (Ectyodoryx) Lundbeck, 1909 (Coelosphaeridae, Poecilosclerida, Demospongiae) from Southern Chile: new species and a discussion of morphologic characters in the subgenus - Fernandez, Julio C.c.; Cárdenas, César A.; Bravo, Alejandro; Lôbo-Hajdu, Gisele; Willenz, Philippe; Hajdu, Eduardo (Zootaxa, 2016)
Our ongoing studies of the Chilean sponge fauna revealed four new species of Lissodendoryx (Ectyodoryx) that are described here, including three from the fjord’s region (< 30 m depth, L.(E.) ballena sp. nov., L. (E.) corrugata sp. nov.,      L. (E.) coloanensis sp. nov.), and one from the deep waters off Diego Ramírez Archipelago (ca. 2000 m, L. (E.) diegoramirezensis sp. nov.). In addition, the type of L. (E.) anacantha was revised and found to bear much larger acanthostyles than originally reported. Our results revealed skeletal architectures quite distinct from that reported from the type species of L. (Ectyodoryx), and not predicted in the current diagnosis of Lissodendoryx, requiring an amended diagnosis. Ectosomal megascleres also set the majority of the new species apart from the type species of L. (Ectyodoryx), which does not have terminally microspined (sub)tylotes. This character is widespread in Lissodendoryx and might be pointing to phylogenetic affinities across the current subgeneric arrangement. Further morphologic characters and alternative phylogenetic scenarios are discussed, including hymedesmiid and myxillid affinities of the species described here.